Cultural-Based Culinary Product Marketing Communication: A Case Study of Pempek Salisah in Blitar, East Java - Sari, Rohmah Nia Chandra; Rosyidah, Ulfah; Arlinda, Silvi Aris (JUSS (Jurnal Sosial Soedirman), 2025)
This study aims to examine the integrated marketing communication strategy employed by Kedai Pempek Salisah in introducing pempek—a traditional Palembang dish—in Blitar, a city with a distinct cultural background. Drawing on perception theory and integrated marketing communication, and using a descriptive qualitative approach within a constructivist paradigm, the study finds that Salisah's success lies in preserving the cultural identity of pempek while adapting to local tastes. Consistent communication strategies through social media, word of mouth, taste adjustments, and relatable promotional language help build emotional connections with consumers. The study concludes that effective intercultural communication in culinary marketing requires a balance between cultural preservation and contextual adaptation.